Constraints limiting the effectiveness of extension agents in disseminating climate-smart agricultural practices among rice farmers in north-Central Nigeria - Ojo, Ibukun Elizabeth; Akangbe, Jones Adebola; Kolawole, Ebenezer Ayorinde; Owolabi, Ayotunde Olayinka; Obaniyi, Kayode Samuel; Ayeni, Matthew Durojaiye; Adeniyi, Victoria Abosede; Awe, Toluwase Eniola (Frontiers in Climate, 2024)
Climate-smart agricultural practices play a crucial role in achieving national food security and development goals, and the significance of extension agents in this endeavor is invaluable. In view of this, this study investigated the constraints limiting the effectiveness of extension agents in disseminating climate-smart agricultural practices to rice farmers in North-central, Nigeria. The study specifically examined the socioeconomic characteristics of the extension agents, the dissemination pathways employed by them, constraints limiting the extension agents from effectively disseminating climate-smart agricultural practices, and the factors that influence their constraints. Data for the study were collected using a well-structured questionnaire administered to a total of 88 respondents selected through a multistage sampling procedure. Data analysis was done using descriptive statistics and Pearson product–moment correlation. The result showed that the respondents had a mean age of 48 years, the majority were males (93.2%), married (95.5%), and (85.2%) had tertiary education. Dissemination pathway/ method mostly used by the extension were; farm and home visits (𝑥̅ = 1.73), result demonstration (𝑥̅ = 1.66), and methods demonstration (𝑥̅ = 1.58). The constraints impeding the extension agents in disseminating CSA practices were; insufficient number of extension workers to provide services for a large number of farmers (𝑥̅ = 1.87), lack of incentives for staff motivation (𝑥̅ = 1.83), inadequate means of transportation (𝑥̅ = 1.83), were ranked 1st,2nd, and 3rd, respectively. There was a negative significant correlation (p = 0.05) between the number of training and personal constraints, as well as institutional constraints (p = 0.017) in the dissemination of climate-smart agricultural practices. Therefore, it is recommended that extension agents receive periodic training and incentives such as awards, cash rewards, promotions, and staff recognition from government bodies to enhance their performance.